Fibrosis retroperitoneal asociada a neoplasias malignas. Serie de Casos Clínicos. - Vega, Jorge; Ceriani, Alejandro; Jensen, Daniela (Revista Médica de Chile, 2014)
Retroperitoneal fibrosis (RPF) is uncommon. Eight percent of cases are associated with malignancies. The pathogenesis of cancer related RPF (MRPF) is unknown. It may be originated from a desmoplastic reaction of the retroperitoneum to the presence of malignant cells, to the action of cytokines secreted by the tumor or a reactive inflammation. MRPF may also be a consequence of antineoplastic therapy (surgery, radiotherapy and chemotherapy). We report eight cases of MRPF associated with breast, cervix, thyroid, kidney and retroperitoneal cancer. In four patients, retroperitoneal tissue biopsy was performed, showing the typical findings of idiopathic RPF. In 6 patients MRPF appeared one to 15 years after cancer diagnosis and in two, it appeared simultaneously. The clinical presentation, course and therapeutic response are described. Six patients were treated with steroids alone and five with steroids associated with colchicine.